Juridical Analysis on Responsibility of Notaries Against Counterfeiting Description Existence in An Authentic Agreement - Siska Dwi Astuti July; Khusen Martono; Sri Endah Wahyuningsih (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Article 1 Paragraph (1) of Act No. 2 of 2014 concerning Notary Office constitution that notaries are public officials, the authority to make the Act Authentic legitimate. Unfortunately in today's world that is filled by the desire of economic excess, not a few people on the mountain doing the wrong thing in order to enrich themselves, unfortunately including the notary who had exalted position in society as one of the authorities, instead of showing the action sublime them Authentic Act falsified. This study aims to clarify how the rule of law based on the positive law in Indonesia about such actions. Using normative juridical approach, and statutory approach, exploiting all the laws that have a correlation with the observed cases. To find practical application, researchers used the District Court of Semarang No. 676 / Pid.B /2017 PN.Smg The conclusion showed notary who forged authentic action violates the Notary Code and morally can not punish a criminal by Notary Code by the Board of Supervisors, but no conclusions about the case in the District Court ruling Semarang. While the notary may be punished criminally if proven wrong by article 264 of the Criminal Code no violation of law in Indonesia.Keywords: Notary; Authentic Agreement; Suspect.